2013
DOI: 10.15580/gjemps.2013.1.111212251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental Impact Assessment System in Nigeria

Abstract: Environmental impact assessment (EIA) came into being in Nigeria with promulgation of the Act establishing three independent EIA systems-the EIA Decree 86 (1992), the Town and Country Planning Decree 88 (1992) and the Petroleum Act (1969). Despite a sound legal basis and comprehensive guidelines, evidence suggests that EIA has not yet evolved satisfactorily in Nigeria, as the current system amounts to duplication of efforts and cost. An evaluation of the EIA system against systematic evaluation criteria, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…After the dumping of toxic waste in Koko Port in 1988, the country jumpstarted a series of environmental legislative policies, including the eventual requirement for an EIA [38]. The "knee jerk" legislative efforts led to the development of three EIA systems: the EIA Decree 86 (1992), the Town and Country Planning Decree 88 (1992) and the Petroleum Act (1969) [38,39]. Several evaluations of the state of EIA in Nigeria have concluded that the system duplicates efforts due to similar requirements found in these legislative acts: there are too many conflicts of interest among EIA governing authorities, there exist important oversights in the quality of execution at all stages, there is a severe lack of public participation at all stages, and deficiencies in the competence of EIA practitioners.…”
Section: Example Of the Nigerian Casementioning
confidence: 99%
“…After the dumping of toxic waste in Koko Port in 1988, the country jumpstarted a series of environmental legislative policies, including the eventual requirement for an EIA [38]. The "knee jerk" legislative efforts led to the development of three EIA systems: the EIA Decree 86 (1992), the Town and Country Planning Decree 88 (1992) and the Petroleum Act (1969) [38,39]. Several evaluations of the state of EIA in Nigeria have concluded that the system duplicates efforts due to similar requirements found in these legislative acts: there are too many conflicts of interest among EIA governing authorities, there exist important oversights in the quality of execution at all stages, there is a severe lack of public participation at all stages, and deficiencies in the competence of EIA practitioners.…”
Section: Example Of the Nigerian Casementioning
confidence: 99%
“…The EIA is generally used to ensure that potential environmental hazards on public health and property are forecasted and mitigating steps taken during the design stage of a project. 147 Following this principle, the Nigerian EIA Act 1992 directs that before any person 148 undertakes any project, they must first empirically consider any matter that "may likely or to a significant extent affect the environment or have an environmental effect on those activities…" 149 The Act further empowers the NESREA to make regulations for the effective implementation of its provisions. However, the Act does not in practice implement the principle of precautionary approach.…”
Section: National Environmental Standard and Regulations Enforcementmentioning
confidence: 99%
“…When a proponent proposes a project or programme, an assessment is conducted in line with prevailing regulations and conditions, which consists of sequential processes that lead to the development of an environmental impact statement (EIS) containing details of the potential impact of the project on the environment along with possible mitigation measures (Nwafor, 2006). The EIS guides the regulator's decision during the authorization process whether to redesign, adopt a possible alternative, cancel or approve with associated conditions for managing the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Morisson-Saunders and Art (2001) argue that without follow-up, EIA may remain an approval seeking exercise. Wood (2003) and Nwafor (2006) support this notion adding that the EIA process does not end with production of the EIS on the potential impacts of a project and related proposed mitigations. Nigeria and other EIA jurisdictions of the world like South Africa, Western Australia, Kuwait, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation